Evaluasi Decline Curve Analysis untuk Peramalan Produksi dan Estimated Ultimate Recovery (EUR) pada Lapangan SWIFT Sumur S-6 - Benaputri Roswati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Oil production decline must be evaluated to estimate future well performance and Estimated Ultimate Recovery (EUR). This study aimed to evaluate the Exponential, Harmonic, and Hyperbolic Decline models for SWIFT Field Well S-6 and determine the most suitable model for production forecasting. Decline Curve Analysis was applied to historical production data from day 1 to day 1245, which were converted into monthly production data and divided into Trend 1 and Trend 2. For the Hyperbolic Decline model, the b values for Trend 1 and Trend 2 were determined using a trial-and-error approach, and model performance was evaluated using qi, Di, b, RMSE, and R². The results showed that the Hyperbolic Decline model provided the best fit for Trend 1, while the Harmonic Decline model was the best for Trend 2 with an RMSE of 2.0945 STB/day and an R² of 0.9282. The Harmonic Decline model was selected for production forecasting until the 5 STB/day economic limit, resulting in an Estimated Ultimate Recovery of 241,732.43 STB.